WYPRAWA CESARZA SEPTYMIUSZA SEWERA DO BRYTANII W LATACH 208-211 W ŚWIETLE ŹRÓDEŁ HISTORIOGRAFICZNYCH I NUMIZMATYCZNYCH - Daria Janiszewska-Sieńko (In Gremium. Studies in History, Culture and Politics, 2012)
THE 208-211 EXPEDITION OF EMPEROR SEPTIMIUS SEVERUS TO BRITAIN IN HISTORIOGRAPHICAL AND NUMISMATIC SOURCESThe expedition emperor Septimius Severus made to Britain in years 208-211 was the last militarycampaign in the life of this first representative of the Severus dynasty. Its impact can be found in nu-merous historiographical, numismatic and inscriptive sources. This article deals with the comparison ofthe little source material found in the works of Roman historians Cassius Dio and Herodian with theinformation passed on to us by the imperial mint. The campaign had a few objectives. First of all, itaimed at taming the rebellious Caledonian people living in northern Britain, putting the administrationin Roman Britain in order and rebuilding the local limes. The emperor's desires to strengthen hisimage of a victorious leader and to clearly mark his sons Karakalla and Geta as his successors were alsoimportant. The fights with the locals did not have a tangible effect (the Romans failed to subdue thewhole of Britain) but undoubtedly had a propaganda character as planned by the emperor. SeptimiusSeverus died at the beginning of 211 in Eburacum and not long after his sons ended the campaign andwent back to Rome as equal emperors of Imperium Romanum.